ANALISIS FINANSIAL INDUSTRI PENGOLAHAN GULA MERAH DI DESA PENAGO II KECAMATAN ILIR TALO (Kajian : Industri Rumah Tangga “Kelompok Sumber Rezeki” di Desa Penago II Kec. Ilir Talo Kabupaten Seluma) - Melinda Triasmadita (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2016)
Nira water  in coconut plants containing 7.5 to 20% sugar content so that it can be processed brown sugar. The purpose of this study was to identify the general picture industry, BEP and feasibility analysis brown sugar processing industry. Descriptive analysis was used as the analysis method in this research to identify the general picture industry, BEP (Break Event Point) analysis, and Return Cost Ratio (R / C Ratio) analysis. The results revealed that general picture of brown sugar processing industry in Penago II village deserves to be developed because it can improve the living standards of economy community's as a craftsman brown sugar, BEP production obtained brown sugar industry amounted to 2682.78 kg/year the price of BEP Rp. 7804.28/kg, Value of Return Cost Ratio R / C ≥ 1 is equal to 1.45.  Keywords: Brown Sugar Processing Industry, Financial Analysis